2021
DOI: 10.1016/j.amsu.2021.01.037
|View full text |Cite
|
Sign up to set email alerts
|

The role of postoperative antibiotics in preventing surgical site infections in uncomplicated appendicitis

Abstract: A best evidence topic has been constructed using a described protocol. The three-part question addressed was: In patients who underwent appendicectomy for uncomplicated appendicitis is the use of postoperative antibiotics associated with lower rates of surgical site infections? The search has been devised and 6 studies were deemed to be suitable to answer the question. The outcome assessed was the efficiency of postoperative antibiotic therapy in decreasing the rate of surgical site infections in un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
3
0
2
Order By: Relevance
“…The commonly affirmed practice is to stop postoperative antibiotics within 24 h in patients with uncomplicated AA[ 85 , 86 ], which is widely considered acceptable since source control is achieved. Abounozha et al [ 87 ] reported that postoperative antibiotics in patients with uncomplicated AA do not decrease surgical site infections but increase the length of stay and costs[ 87 ].…”
Section: Management Of Appendicitismentioning
confidence: 99%
“…The commonly affirmed practice is to stop postoperative antibiotics within 24 h in patients with uncomplicated AA[ 85 , 86 ], which is widely considered acceptable since source control is achieved. Abounozha et al [ 87 ] reported that postoperative antibiotics in patients with uncomplicated AA do not decrease surgical site infections but increase the length of stay and costs[ 87 ].…”
Section: Management Of Appendicitismentioning
confidence: 99%
“…Complicated appendicitis must meet at least 1 of the following criteria: visible hole in the appendix, fecalith outside the appendix, abscess, or diffuse fibrinopurulent exudate throughout the abdominal cavity. Single-institution studies have supported the notion that GSE appendicitis can be treated as uncomplicated (no postoperative antibiotics) without increasing SSI rates; however, these findings have not been embraced widely …”
mentioning
confidence: 99%
“…Single-institution studies have supported the notion that GSE appendicitis can be treated as uncomplicated (no postoperative antibiotics) without increasing SSI rates 3,4 ; however, these findings have not been embraced widely. 5,6 In this issue of JAMA Surgery, Cramm and colleagues 7 report the first, large, multicenter study demonstrating that postoperative antibiotics do not reduce risk of SSI in patients with GSE appendicitis. They used NSQIP-Pediatric data supplemented by medical record review from 16 centers to compare SSI rates in children with uncomplicated, GSE appendicitis who did and did not receive postoperative antibiotics.…”
mentioning
confidence: 99%
“…También menciona que el uso de antibióticos por 3 días resulta efectivo para disminuir las probabilidades de una infección como un tratamiento por 5 días. 49 Abounozha S, et al 52 (2021) En un estudio sobre "El papel de los antibióticos posoperatorio en la prevención de infección del sitio quirúrgico en la apendicitis no complicada", refiere que el antibiótico posoperatorio no disminuye los casos de infección de sitio operatorio de apendicitis aguda complicada, pero aumenta los costos y la morbilidad del paciente.…”
Section: Tratamientounclassified
“…75 El tratamiento antibiótico o la apertura de la herida es necesario en el caso de las infecciones de sitio operatorio superficial y la infección de sitio operatorio profunda, se da porque en el interior de la cavidad peritoneal se formará un cúmulo de líquido lo que llevaría a realizar un drenaje. 52 En un estudio de ensayos y controles aleatorios realizado en 2017 por Moosavi S. 76 , donde se incluyó 152 pacientes. Llego a la conclusión que el uso de antibióticos preoperatorio fue eficiente para disminuir las tasas de ISO posterior a una apendicetomía.…”
Section: Prevención De Infección De Sitio Operatoriounclassified